2011
DOI: 10.1002/ijc.26018
|View full text |Cite
|
Sign up to set email alerts
|

Integrin‐dependent response to laminin‐511 regulates breast tumor cell invasion and metastasis

Abstract: The basement membrane protein, laminin (LM)-511, is a potent adhesive and migratory substrate for metastatic breast tumor cells in vitro. Its expression correlates with tumor grade and metastatic potential in vivo. These observations suggest that responsiveness to autocrine or paracrine-derived LM-511 may be an important property regulating breast cancer metastasis in vivo. To address this, we compared the metastatic potential of 4T1 mammary carcinoma cells to that of 4T1 variants isolated by repeated chemotac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 39 publications
3
65
0
1
Order By: Relevance
“…Our study demonstrated that LM-511 is a potent adhesive substrate for breast tumour cells and promotes their migration and invasion [9]. The relevance of breast tumour cell interaction with LM-511 in metastasis was further supported by the isolation of aggressive bone metastatic tumour variants using a selection protocol based on their rapid migratory response towards LM-511 in vitro [16]. The enhanced metastatic capacity of these variants was associated with increased expression of b1 and b4 integrin/laminin receptors [16].…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Our study demonstrated that LM-511 is a potent adhesive substrate for breast tumour cells and promotes their migration and invasion [9]. The relevance of breast tumour cell interaction with LM-511 in metastasis was further supported by the isolation of aggressive bone metastatic tumour variants using a selection protocol based on their rapid migratory response towards LM-511 in vitro [16]. The enhanced metastatic capacity of these variants was associated with increased expression of b1 and b4 integrin/laminin receptors [16].…”
Section: Introductionmentioning
confidence: 79%
“…Our own investigation revealed a role for LM-511 but not LM-111 or -332 in the regulation of breast cancer metastasis [5,9,16]. Here, we sought to test LMa5 chain-derived peptides, previously shown to possess cell binding activity [19,20,41], for their ability to modulate LM-511-dependent breast tumour cell responses in vitro and metastasis in vivo.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations